2019
DOI: 10.3389/fnhum.2019.00156
|View full text |Cite
|
Sign up to set email alerts
|

Does Movement Matter? Prefrontal Cortex Activity During 2D vs. 3D Performance of the Tower of Hanoi Puzzle

Abstract: In the current study, we used functional near-infrared spectroscopy (fNIRS) to compare prefrontal cortex (PFC) activity in adults as they performed two conditions of the Tower of Hanoi (ToH) disk-transfer task that have equivalent executive function (EF) but different motor requirements. This study explored cognitive workload, here defined as the cognitive effort utilized while problem-solving by performance output. The first condition included a two-dimensional (2D) computerized ToH where participants complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 108 publications
0
13
0
3
Order By: Relevance
“…Signal acquisition was optimized by 1) cleaning the participants' forehead with an alcohol swab prior to positioning the sensor band, 2) excluding any hair between the sensor and the participants' forehead, 3) adjusting Gain and LED Current until raw wavelength signal was verified to be between 40 -4000 mV, and 4) reducing the ambient light in the testing room. Each participant began with a 1-minute resting period in which they sat with their eyes open looking at a black cross sign on the computer screen [14].…”
Section: Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…Signal acquisition was optimized by 1) cleaning the participants' forehead with an alcohol swab prior to positioning the sensor band, 2) excluding any hair between the sensor and the participants' forehead, 3) adjusting Gain and LED Current until raw wavelength signal was verified to be between 40 -4000 mV, and 4) reducing the ambient light in the testing room. Each participant began with a 1-minute resting period in which they sat with their eyes open looking at a black cross sign on the computer screen [14].…”
Section: Protocolmentioning
confidence: 99%
“…Data were subsequently converted to changes in concentration through the modified Beer-Lambert law [48] and depicted into 4 outcome measures: change in oxygenated hemoglobin (∆HbO), change in deoxygenated hemoglobin (∆HbR), total change in hemoglobin (∆HbT) and total change in oxygenation (∆Oxy). We restricted our analysis to ∆HbO because preliminary analysis from our previous work found a high correlation among ∆HbO, ∆HbR, ∆HbT, and ∆Oxy [14].…”
Section: Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The planning and execution of walking involves several cortical and subcortical areas [ 19 , 20 ]. The activation of the brain areas, due to motor planning and execution, can be measured using several image and signal acquisition methods, including magnetoencephalography [ 21 , 22 ], functional magnetic resonance imaging [ 23 , 24 ], functional near-infrared spectroscopy [ 25 , 26 ], and EEG [ 27 , 28 ]. Among these modalities, EEG has several distinct advantages in assessing brain responses to locomotion.…”
Section: Introductionmentioning
confidence: 99%
“…It was noted that motor planning is an ability about anticipating motor demands and PFC plays a critical role in motor planning [23]. Extensive neuroimaging researches have demonstrated that concurrent activation in the PFC and MC while motor planning [24], [25] and execution [26].…”
Section: Introductionmentioning
confidence: 99%